Sensitivity stadies of the switch jitter effect on the square pulse LTD with three harmonics; Известия вузов. Физика; Т. 57, № 12/2 - Alexeenko V. M. Vitaliy Mihaylovich; Mazarakis M. G. Mihail G.; Kim A. A. Aleksandr Andreevich; Kondratiev S. S. Sergey Sergeevich; Vasiliev S. V. Sergey Valerievich; Sinebryukhov V. A. Vadim Anatolievich; Leckbee Joshua; Kiefer M. L. Mark L. (2014, 2014)
Заглавие с экрана